HUBUNGAN INTENSITAS PEMANFAATAN KONTEN KESEHATAN REPRODUKSI PADA MEDIA SOSIAL INSTAGRAM TERHADAP TINGKAT PENGETAHUAN REMAJA DI PULAU JAWA - Farasiva Indiani Rajasa; Bagoes Widjanarko; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2020)
Advances of information and communication technology that can never be limited by time and space increasing the number of internet users in Indonesia. Java has the most internet users (55% of the total), with Instagram as one of the social media that mostly used by adolescents (37.3%). Adolescence, transitional phase of growth between childhood and adulthood, is the age when the reproductive system begins to change and physical maturation happens. There are times when adolescents feel uncomfortable to discuss sexual and reproductive health issues. The existence of social media makes it easier for adolescents to find information about reproductive health without any direct interactions between one another. This research aims to analyze the relationship of intensity reproductive health content usage on Instagram with adolescents’ level of knowledge in Java. This research employs a quantitative research design, using an online questionnaire with a cross-sectional study, and the number of respondents, 383 precisely, is determined by using a purposive sampling technique. The results showed that 63.2% of the respondents had a high-intensity use of reproductive health content on Instagram and 55.1% of the respondents had a lack of reproductive health knowledge. Based on the results of the bivariate analysis using Chi-square test, there is a relationship between the intensity of reproductive health content usage on Instagram (p-value 0,000) with adolescents’ level of knowledge in Java.